Potency of Endophyte Microbes as an Antagonistic Agent for Colletotrichum capsici Causes Anthracnose Disease in Cayenne pepper (Capsicum frustescens) - Afifah, Zahroul; Utami, Ulfah (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2017)
Background: An anthracnose disease caused by pathogenic fungal Colletotrichum capsici has been attacking the cayenne plants either harvested or has not been harvested. This disease must be handled appropriately and quickly because it can reduce the production of chili up to 90%. Recently, anthracnose disease prevention still use chemical fungicide that if applied for long time will cause new impact for environment. Objective: Trichoderma and Bacillus cereus endophytes may be used as antagonistic agents for C. capsici pathogens because they have various antibiotic compounds. Methods: This research uses experimental method. The stages of this study include sterilization of tools and materials, preparation of culture media of fungal and bacteria, rejuvenation of endophytic microbe culture Trichoderma sp. and Bacillus cereus, rejuvenation of Â C. capsici pathogen, antagonistic test in vitro using dual culture method. Result and conclusion: The results of in vitro antagonistic tests showed that inhibition percentage of Trichoderma treatment (96%) and combination treatment Trichoderma and B. cereus (97%) is not significantly different. While in B. cereus treatment (11, 88%) significantly different with all of treatments. Endophytes are shown by its dominating growth in petri dishes than C. capsici pathogen or B. cereus endophytes. Furthermore,for endophytes Trichoderma sp continued on in vivo test because it was most effective.The result for incubation period is 3 days after inoculation compared with negative control 2 days. For disease incidence 100%, and for disease intensity that is 61,25% compared with negative control equal to 88,75%.